Science for art: multi-years' evaluations of biocidal efficacy in support of artwork conservation - Bartoli, Flavia; Isola, Daniela; Casanova Municchia, Annalaura; Kumbaric, Alma; Caneva, Giulia (Frontiers in Microbiology, 2023)
In recent decades, the relationship between Science and Art has been gradually strengthening by applying technologies for the diagnostic and conservation of artworks, as well as for the valorization, but also by their realization. In such context, starting from the Spring of 2014, we performed in situ experimentation to support the duration of the unusual graphical artwork of William Kentridge on the Lungotevere embankments, whose creation was scheduled in the following years. Various combinations and concentrations of three different biocides (Algophase, Biotin R, Preventol R80) and two water repellents (Hydrophase surfaces, Silo 111) were applied on 34 test areas. The planned works of “Triumph and Laments of Rome” were later realized in 2016, only selectively removing through pressurized water the black biological colonization mainly composed of cyanobacteria. Finally, the artist preferred to leave his artwork to a natural fading. Our previous monitoring, analyzing image and colourimetric variations of such drawings, showed a duration of 4 years in the natural condition of recolonization. In the present paper, the recolonization of treated and control areas, analyzed with the same methods, showed a maximum duration of 3 years longer than under natural conditions in the case of Preventol R80® and Biotin R® plus Silo 111®. Indeed, the tested solutions showed differential effectiveness and multiple possibilities of use to support the maintenance of the artwork following the artist's wishes.